Ciencias de la educación abiertas: Las prácticas de sus investigadores y algunas proyecciones para Colombia - Vallejo-Sierra, Ruth-Helena; Pirela-Morillo, Johann-Enrique; Tunjano-Huertas, Wilintong (Revista Científica, 2023)
Nowadays, educational research faces different changes. One of the most urgent is the articulation with the principles and criteria of open science, which aim to expand the models, scenarios and platforms related to the production, circulation, use and transfer of educational knowledge. To approach the current panorama and establish some projections for Colombia, the results of the research “open science practices of Colombian researchers” were analyzed, particularly of the 122 researchers in the educational sciences. It was found that, in the design of research, especially information is consulted in open resources. And low percentages in relation to the construction of research agendas together with communities and institutions. In the design of the methodology, low percentages of replication of investigative methods and techniques are reported. Data management is one of the practices with the lowest results, as well as public communication of science. The conclusions place the emphasis on promoting open science in: the training processes of science actors, throughout the educational cycle, especially in the teaching of research and scientific vocations, and in the recognition processes of curricular projects. from all areas of knowledge.